2022
DOI: 10.3389/fphar.2022.916769
|View full text |Cite
|
Sign up to set email alerts
|

β2-Microglobulin is a Novel and Reliable Biomarker for Predicting Ischemic Stroke Recurrence: A Prospective Cohort Study

Abstract: Immune and inflammatory mechanisms play key roles in the development and outcome of acute ischemic stroke (AIS). β2-Microglobulin (β2M) is the light chain of major histocompatibility complex-1 (MHC-1), which can directly and quickly reflect the immune and inflammatory state of the body. Previous studies have shown a close relationship between β2M and AIS, but its relationship with the recurrence of AIS has not been reported. This study attempted to explore the relationship between β2M and the recurrence of AIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…CroR@aB2MG targets senescent cells effectively, with the direction of an anti-B2MG antibody. The expression of blood-borne B2MG, a biomarker for cancer and many inflammatory diseases [47][48][49] has been found positively correlated with age, the levels of p16 ink4a , IL-1β and IL-6, and the oxidative stress [50,51]. This is in line with our results, as CroR@aB2MG-mediated NIR irradiation reduced DOX-boosted senescence marked by the enhanced expression of p16 ink4a , p53, DcR2, FOXO4 and the loss of lamin B1.…”
Section: Discussionsupporting
confidence: 90%
“…CroR@aB2MG targets senescent cells effectively, with the direction of an anti-B2MG antibody. The expression of blood-borne B2MG, a biomarker for cancer and many inflammatory diseases [47][48][49] has been found positively correlated with age, the levels of p16 ink4a , IL-1β and IL-6, and the oxidative stress [50,51]. This is in line with our results, as CroR@aB2MG-mediated NIR irradiation reduced DOX-boosted senescence marked by the enhanced expression of p16 ink4a , p53, DcR2, FOXO4 and the loss of lamin B1.…”
Section: Discussionsupporting
confidence: 90%
“…A nested case-control study based on data from 473 patients with ischemic stroke and 473 controls demonstrated that high serum levels of β2M were associated with an increased risk of ischemic stroke among women, especially in patients who had experienced thrombotic stroke [18]. Hu et al studied 135 patients with ischemic stroke and reported that high β2M levels in serum upon admission increased the risk of recurrence approximately 3 years after the initial event [29]. Finally, a large prospective study revealed that β2M was signi cantly associated with the occurrence of stroke in patients with asymptomatic carotid atherosclerosis at the 3-year follow-up [30].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma B2M could also be used to evaluate the extent and degree of acute cerebral infarction (Li and Zhou 2016 ). Additionally, AIS patients with plasma B2M levels over 2.31 mg/L are more susceptible to disease recurrence, which suggests B2M may act as a potential biomarker for predicting recurrence in these patients (Hu et al 2022 ).…”
Section: Role Of B2m In Specific Cns Diseasesmentioning
confidence: 99%